An Epistemic Perspective on Consistency of Concurrent Computations - Gleissenthall, Klaus v.; Rybalchenko, Andrey (Concurrency Theory (CONCUR), 2013)
Consistency properties of concurrent computations, e.g., sequential consistency, linearizability, or eventual consistency, are essential for devising correct concurrent algorithms. In this paper, we present a logical formalization of such consistency properties that is based on a standard logic of knowledge. Our formalization provides a declarative perspective on what is imposed by consistency requirements and provides some interesting unifying insight on differently looking properties.